Atopy, immunological changes, and respiratory function in bronchiectasis. - Murphy, M B (1984)
Cystic fibrosis has been reported to be associated with an increased prevalence of atopy and reversible airways obstruction. To determine whether such features can also result from other chronic suppurative lung infections, we studied 23 patients with proved bronchiectasis, and 23 age and sex matched normal controls. A personal or family history of atopy was reported with equal frequency in the two groups. Although the groups displayed a similar prevalence of positive immediate hypersensitivity skinprick test responses, the positive patients reacted to more antigens (p less than 0.05) and had larger weal diameters (p less than 0.01) than the positive controls. Other indices, such as blood eosinophil counts and serum IgE, did not differ significantly. Serum concentrations of immunoglobulins G, A, and M and of the four IgG subclasses tended to be higher in patients than controls, but only in the case of IgA (p less than 0.01) was this difference significant. No case of IgG subclass deficiency was noted. The patients displayed significant airflow obstruction, the mean basal one second forced expiratory volume (FEV1), forced vital capacity (FVC), and peak expiratory flow rate (PEFR) being 67%, 77%, and 67% of their predicted values. There was evidence of a significant reversible obstructive component in that FEV1 or PEFR or both increased by 15% or more in nine of the 23 patients after inhalation of fenoterol, the mean increases in FEV1, FVC, and PEFR for the whole group being 9.5%, 11%, and 16.9%. These results indicate that while bronchiectasis provokes a hyperimmune response it differs from cystic fibrosis in that there is no significant increase in the prevalence of atopy. The finding of reversible airways obstruction, however, suggests that bronchodilators may be useful adjuncts to treatment.